2001
DOI: 10.1128/aac.45.6.1872-1875.2001
|View full text |Cite
|
Sign up to set email alerts
|

Activities of Hexadecylphosphocholine (Miltefosine), AmBisome, and Sodium Stibogluconate (Pentostam) against Leishmania donovani in Immunodeficient scid Mice

Abstract: In both scid and BALB/c mouse-Leishmania donovani models, hexadecyphosphocholine (miltefosine) and AmBisome had similar levels of activity. In contrast, sodium stibogluconate (Pentostam) was significantly less active against L. donovani in scid mice than in BALB/c mice. The in vitro anti-leishmanial activity of miltefosine was similar in peritoneal macrophages derived from both scid and BALB/c mice, whereas Pentostam and AmBisome were significantly more active in the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 32 publications
7
55
0
5
Order By: Relevance
“…This same inflammatory mechanism also supports the efficacy of conventional antileishmanial chemotherapy-T cells and endogenous IL-12 and IFN-␥ are required for expression of the visceral leishmanicidal action of pentavalent antimony (Sb) in experimental infection (12,40,41). As judged by results with additional cytokine gene-disrupted mice, TNF and IL-4 also optimize the host response to Sb (2,42).…”
mentioning
confidence: 64%
“…This same inflammatory mechanism also supports the efficacy of conventional antileishmanial chemotherapy-T cells and endogenous IL-12 and IFN-␥ are required for expression of the visceral leishmanicidal action of pentavalent antimony (Sb) in experimental infection (12,40,41). As judged by results with additional cytokine gene-disrupted mice, TNF and IL-4 also optimize the host response to Sb (2,42).…”
mentioning
confidence: 64%
“…The basis for this lack of activity of pentavalent antimonials has been explored in immunodeficient mouse models for which the effects are probably due to deficiencies of both Th1-cell-mediated and macrophage responses (109). Experimental models have shown that the antileishmanial activity of pentamidine is also T-cell dependent whereas those of amphotericin B and miltefosine are T-cell independent (61,108). Irrespective of the findings of the experimental models, it is now known that intact immunity holds the key to the curative ability of antileishmanial drugs, including amphotericin B.…”
Section: Host Factors Host Immune Statusmentioning
confidence: 99%
“…In India, where resistance to antimonial agents is very high, miltefosine has been used since 1998 for the treatment of Visceral Leishmaniasis (VL) produced by L. donovani 7,24 . This has motivated its evaluation for the treatment of other leishmaniasis 25 .…”
Section: Introductionmentioning
confidence: 99%